Penampilan Produksi Anak Ayam Buras yang Dipelihara pada Kandang Lantai Bambu dan Litter - Azis, Abdul (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2006)
The objective of the experiment was to study performance of buras chickens reared on bamboo floor and  litters system. One hundred unsex buras chickens age 7 days were used in this research that reared into 2 floor system as treatment. The treatments were bamboo floor and litter floor. The result of the experiment showed that feed intake and body growth of buras chicks reared on litter floor higher (P<0.01) than bamboo floor during 7 to 28 days of age. There were no difference litter and bamboo floor system on feed  intake,  body  growth  and  feed  convertion  during  28  to  56  days  of  age.  It  was concluded that performance of buras chicks reared on litter floor system had better than